(untitled) (Global Journal of Human-Social Science, 2020)
This paper focuses on the perception of Kashmiri Pandit participants on Sufism and Rishi culture of Kashmir. This generation of Kashmiri Pandit have lived significant years of their lives in Kashmir and have remained closely associated with the Sufi and Rishi traditions of Kashmir. They have had immense faith in the shrines of Sufi saints. The shrines of Sufi saints were revered by Kashmiri Pandits not only in a similar manner but more than their Kashmir i Muslim compatriots as told by the o lder generation of Kashmiri Muslims participants. Kashmiri Muslims had deep faith in these shrines. That has also contributed towards strengthening the of bond of brotherhood/bahichara between Kashmiri Muslims and Kashmiri Pandits, as both had close association with these practices irrespective of their own religious faiths.